From Savannas to Settlements: Exploring Cognitive Foundations for the Design of Urban Spaces - Brown, M. Gordon; Lee, Charles C. (Frontiers in Psychology, 2016)
Urban configurations in developing countries have become the subject of urban design, with good design promoting economic benefits. Yet, the common practice of urban design lacks a principled scientific foundation. In this respect, cognitive neuroscience could provide a unique perspective and potential foundational insights regarding how embodied cognition links configuration with movement. Although the neural networks that underlie navigation abilities in the brain have been extensively studied, the manner in which these networks might best constrain urban configurations has not been examined specifically. Moreover, it remains an open issue whether the neurological development and functional topographies in the brain that could potentially constrain such urban configurations might also replicate the geometric structures of those environments that were the cradle of human evolution. We propose then that a potential agenda for experimentation and debate could focus on neurological underpinnings of movement choices in urban places. Such an agenda would benefit from bridging a gap between C.P. Snow’s two cultures, i.e. among architects and neuroscientists. Here, we provide a perspective to engender such further dialogue on the design of embodied urban spaces and the potential neural systems that may constrain their design.